Potential therapeutic effects of cyanidin-3-O-glucoside on rheumatoid arthritis by relieving inhibition of CD38+ NK cells on Treg cell differentiation - Hongxing Wang; Shutong Li; Guoqing Zhang; Hui Wu; Xiaotian Chang (Arthritis Research & Therapy, 2019)
Abstract Background CD38+ NK cells are overabundant in rheumatoid arthritis (RA). Cyanidin-3-O-glucoside (C3G) is an inhibitor of CD38. This study investigated the pathogenic role of CD38+ NK cells and the effect of C3G on RA. Methods Rats with bovine type II collagen-induced arthritis (CIA) were injected with C3G. RA synovial fibroblasts (RASFs) or mononuclear cells (MNCs) were cultured with C3G. MNCs were also cocultured with CD38+ NK cells following C3G pretreatment. Results C3G injection significantly alleviated CIA. C3G also significantly increased the level of interleukin (IL)-10 and the regulatory T (Treg) cell proportion, and it decreased the interleukin (IL)-6 and interferon (IFN)-γ levels and CD38+ NK cell proportion in rat peripheral blood and synovial fluid. Additionally, C3G significantly increased RASF apoptosis and decreased RASF proliferation and IL-6 production in the culture medium. Furthermore, C3G stimulated MNCs to increase IL-2 and IL-10 production and the Treg cell proportion, and it caused MNCs to decrease IL-6 and IFN-γ production and the CD38+ NK cell proportion. Although CD38+ NK cells significantly decreased the Treg cell proportion and IL-10 level in MNCs, CD38+ NK cells that had been pretreated with C3G increased the proportion of Treg cells and IL-10 levels and decreased the IL-6 and IFN-γ levels in the coculture. In CD38+ NK cells, C3G significantly increased Sirtuin 6 (Sirt6) expression and the tumor necrosis factor (TNF)-α level, and it decreased natural killer group 2D (NKG2D) expression and the IFN-γ level. However, when CD38+ NK cells were treated with Sirt6 siRNA, C3G did not change the NKG2D expression, the TNF-α level sharply decreased, and the IFN-γ level increased. When MNCs were cocultured with C3G-pretreated CD38+ NK cells in the presence of TNF-α and an anti-IFN-γ antibody, the IL-10+ Treg cell proportion significantly increased. When MNCs were cocultured with C3G-pretreated CD38+ NK cells in the presence of IFN-γ and an anti-TNF-α antibody, the IL-10+ Treg cell proportion sharply decreased. When CIA rats were injected with both C3G and the Sirt6 inhibitor OSS_128167, the rats exhibited joint inflammation and a low Treg cell proportion, but the CD38+ NK proportion was still low. Conclusion C3G has therapeutic effects on CIA and RA. C3G decreased the proportion of CD38+ cells, RASF proliferation, and proinflammatory cytokine secretion, and it increased the Treg cell proportion. C3G also elevated Sirt6 expression to suppress NKG2D expression, increase TNF-α secretion, and decrease IFN-γ secretion in CD38+ NK cells, which stimulates MNCs to differentiate into Treg cells. This study also demonstrates that the inhibition of Treg cell differentiation in MNCs by CD38+ NK cells is a potential cause of the immune imbalance in RA and CIA.